THE RECOVERY OF GAINS FROM A FIDUCIARY'S MISUSE OF TRUST FUNDS. (12th July 2017) - Devonshire, Peter
Abstract : SUPPOSE a trustee misapplies trust funds to purchase property for his own benefit. If the acquired property increases in value, what is the nature of the beneficiaries' claim in respect of those gains? This was recently considered by the Hong Kong Court of Final Appeal in Tang v Tang [2017] HKCFA 3. In 2003 the administrator of an estate (the defendant) purchased property (the "Property"). The purchase was partly funded by the unauthorised use of HK $11.48 m from the estate. Shortly afterwards, the defendant executed a declaration of trust over the Property in favour of his corporate vehicle, Tri-Strong Investment Ltd. The Property was subsequently transferred to this company. Seven months after acquiring the Property, the defendant paid the estate the full amount that had been withdrawn together with interest. In 2005 the estate beneficiaries discovered the defendant's misuse of estate money and commenced proceedings alleging breach of fiduciary duty. By the time the matter was heard, the Property had increased significantly in value.